A novel and safe SmartCap® SC101 to develop the COVID-19 mRNA vaccine STP2104 inducing potent immune responses in humans - Kim, Rachel; Uhm, Tae-Gi; Kim, Jisu; Woo, Dayeon; Kim, Uk-Il; Meng, Xue; Yang, Byounggu; Kim, Suhyeon; Kim, Heejene; Kim, Jonghyeon; Yoon, Sunkyung; Lee, Joo-Young; et al. (Frontiers in Immunology, 2025)
We have developed a 5′-capping library screening (CLS) method using over 30 different novel cap analogues. The optimal 5′-cap for the coronavirus disease 2019 (COVID-19) mRNA vaccine STP2104 was selected and applied. This is the first report to describe the proven safety of the novel cap analogue, SmartCap® SC101, in humans and emphasize the importance of cap selection. STP2104 demonstrates safety, tolerability, and strong immune responses in humans. After confirming its safety through a GLP toxicity study, STP2104 was administered intramuscularly as a two-dose vaccine, separated by 28 days, in COVID-19-naive, healthy adult volunteers. In this multicenter, open-label, dose-escalation, phase I study with 30 participants (18 to 55 years of age), 15 individuals each were assigned to the low-dose (25 μg) and high-dose (50 μg) cohorts. The primary endpoints were the safety and immunogenicity in all cohorts. During the reporting period of the trial, no serious adverse events were reported. A plaque reduction neutralization test demonstrated an at least 21-fold increase in NAb titers from both cohorts when comparing pre-vaccination to 4-week post-second vaccination. These safety and NAb titer interim results support the efficiency and safety of SC101 and the STP2104 mRNA vaccine, including how STP2104 effectively induces NAb titers against SARS-CoV-2.